2007
DOI: 10.1371/journal.pone.0000866
|View full text |Cite
|
Sign up to set email alerts
|

Ubx Regulates Differential Enlargement and Diversification of Insect Hind Legs

Abstract: Differential enlargement of hind (T3) legs represents one of the hallmarks of insect evolution. However, the actual mechanism(s) responsible are yet to be determined. To address this issue, we have now studied the molecular basis of T3 leg enlargement in Oncopeltus fasciatus (milkweed bug) and Acheta domesticus (house cricket). In Oncopeltus, the T3 tibia displays a moderate increase in size, whereas in Acheta, the T3 femur, tibia, and tarsus are all greatly enlarged. Here, we show that the hox gene Ultrabitho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 33 publications
4
83
0
3
Order By: Relevance
“…The interplay of the Hox proteins and the upstream and downstream factors that influence their action has been termed the Hox gene pathway (13). Changes at multiple levels of this pathway are linked to morphological diversity: Changes in the expression of Ubx have been implicated in mouthpart diversity in crustaceans (14-16), evolution of femur shape in Drosophila (17,18), or the evolution of novel appendage morphologies in grasshoppers (19) and waterstriders (20). Changes can also take place in the targets of a Hox gene, as has been suggested for Ubx as the cause for the differences in insect hindwing morphology (21,22), or for Sex combs reduced (Scr) as the cause for the evolution of the dorsal helmet in treehoppers (23).…”
mentioning
confidence: 99%
“…The interplay of the Hox proteins and the upstream and downstream factors that influence their action has been termed the Hox gene pathway (13). Changes at multiple levels of this pathway are linked to morphological diversity: Changes in the expression of Ubx have been implicated in mouthpart diversity in crustaceans (14-16), evolution of femur shape in Drosophila (17,18), or the evolution of novel appendage morphologies in grasshoppers (19) and waterstriders (20). Changes can also take place in the targets of a Hox gene, as has been suggested for Ubx as the cause for the differences in insect hindwing morphology (21,22), or for Sex combs reduced (Scr) as the cause for the evolution of the dorsal helmet in treehoppers (23).…”
mentioning
confidence: 99%
“…The results obtained identified key changes in expression patterns of Ubx that directly correlated with changes in arthropod body plans Angelini and Kaufman, 2005;Averof and Patel, 1997;Castelli-Gair and Akam, 1995;Damen et al, 1998;Mahfooz et al, 2004;Peterson et al, 1999;Stern, 1998;Telford and Thomas, 1998;Zheng et al, 1999). In insects, Ubx expression has also been linked to the differential enlargement of insect hind (T3) legs, which were subsequently confirmed by functional studies (Mahfooz et al, 2007;Mahfooz et al, 2004). As illustrated by these findings, the availability of cross-reacting antibodies are critical in that they provide better phylogenetic sampling by circumventing the laborious process of cloning and characterizing orthologous genes.…”
Section: Introductionmentioning
confidence: 65%
“…Numerous studies have shown that changes in the expression and function of homeotic (hox) genes were pivotal in the evolution of the insect bauplan (Beeman et al, 1993;Beeman et al, 1989;Carroll et al, 2001;Hughes and Kaufman, 2000;Hughes and Kaufman, 2002;Mahfooz et al, 2007;Mahfooz et al, 2004;Rogers et al, 1997;Rogers et al, 2002;Struhl, 1982;Tomoyasu et al, 2005). This insight was primarily based on mRNA expression patterns, however, data on protein accumulation are much more limited.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the expression of these genes can have a role in morphological evolution (e.g. Averof & Patel, 1997;Cohn & Tickle, 1999;Mahfooz et al, 2007), and the expression of Hox genes is conventionally thought to be linked to their organisation in ordered clusters (Duboule & Morata, 1994). The relationship between cluster organisation and gene expression has been most clearly demonstrated in the mouse (Kmita & Duboule, 2003).…”
Section: Genome Evolutionmentioning
confidence: 99%